Java EE 8 development with Eclipse : develop, test, and troubleshoot Java Enterprise applications rapidly with Eclipse - Kulkarni, Ram (Computer software developer) (Packt Publishing, 2018)
Annotation Develop and deploy fully functional applications and microservices utilising Tomcat, Glassfish servers, Cloud and docker in Java EE 8 Key FeaturesExplore the complete workflow of developing enterprise Java applicationsDevelop microservices with Docker Container and deploy it in cloudSimplify Java EE application developmentBook DescriptionJava EE is one of the most popular tools for enterprise application design and development. With recent changes to Java EE 8 specifications, Java EE application development has become a lot simpler with the new specifications, some of which compete with the existing specifications. This guide provides a complete overview of developing highly performant, robust and secure enterprise applications with Java EE with Eclipse. The book begins by exploring different Java EE technologies and how to use them (JSP, JSF, JPA, JDBC, EJB, and more), along with suitable technologies for different scenarios. You will learn how to set up the development environment for Java EE applications and understand Java EE specifications in detail, with an emphasis on examples. The book takes you through deployment of an application in Tomcat, GlassFish Servers, and also in the cloud. It goes beyond the basics and covers topics like debugging, testing, deployment, and securing your Java EE applications. You'll also get to know techniques to develop cloud-ready microservices in Java EE. What you will learnSet up Eclipse, Tomcat, and Glassfish servers for Java EE application developmentUse JSP, Servlet, JSF, and EJBs to create a user interface and write business logicCreate Java EE database applications using JDBC and JPAHandle asynchronous messages using MDBs for better scalabilityDeploy and debug Java EE applications and create SOAP and REST web servicesWrite unit tests and calculate code coverageUse Eclipse MAT (Memory Analysis Tool) to debug memory issuesCreate and deploy microservicesWho this book is forIf you are a Java developer with little or no experience in Java EE application development, or if you have experience in Java EE technology but are looking for tips to simplify and accelerate your development process, then this book is for you.
Previous edition published: 2015.
Keywords: Java (Computer program language); Application software -- Development.; elektronické knihy; electronic books